A systematic review and meta-analysis of surgeries performed for cerebral cavernous malformation-related epilepsy in pediatric patients - Gao, Xiangyu; Yue, Kangyi; Sun, Jidong; Fang, Zheng; Cao, Yuan; Zhao, Boyan; Zhang, Haofuzi; Dai, Shuhui; Zhang, Lei; Luo, Peng; Jiang, Xiaofan (Frontiers in Pediatrics, 2022)
Background: The clinical benefit of surgery for the treatment of cerebral cavernous malformation(CCM)-related epilepsy in pediatric patients is still controversial. Although surgical treatment of CCM-related epilepsy in children is widely recognized, the clinical benefits of controlling the seizure rate must be balanced against the risk of leading to perioperative morbidity. Methods: We conducted a comprehensive search to identify relevant studies via Ovid Medline, Web of Science and PubMed (January 1995-June 2020). The following search terms were used: “hemangioma, cavernous, central nervous system,” “brain cavernous hemangioma,” “cerebral cavernous haemangioma,” “cerebral cavernous malformation,” “epilepsy,” and “seizures.” The seizure control rate and the risk of postoperative adverse outcomes along with their 95% confidence intervals (CIs) were calculated. Results: A total of 216 patients across 10 studies were included in meta-analysis. The results showed that the control rate of epilepsy was 88% (95% CI: 76-95%). Four percent (95% CI: 2-10%) of the patients experienced temporary symptomatic adverse effects following surgical resection, and 3% (95% CI: 0-26%) of the patients developed permanent symptomatic adverse effects in the long-term follow-up after surgical excision of the CCMs. None of the patients died as a result of the CCMs or surgical treatment. Conclusions: Surgery is an effective and safe treatment for cerebral cavernous malformation-related epilepsy in pediatric patients with a low risk of postoperative complications and death.